Alterations in cognitive performance and affect-arousal state during fluctuations in motor function in Parkinson's disease. Issue 5 (May 1984) - Brown, R G; Marsden, C D; Quinn, N; Wyke, M A
Abstract : Sixteen patients with idiopathic Parkinson's disease were selected who were all showing severe fluctuations in motor function ("on-off" phenomenon). Measures of cognitive function and of subjective affect/arousal state were taken on two occasions, once when "on" and once when "off". Twenty-five matched normal controls were also assessed on the same measures. Results revealed, on the average, a drop in cognitive function plus an adverse swing in affect/arousal state, in the patient group in the "off" condition, compared to the levels when "on". Analysis of the data suggested that the main factor associated with cognitive function when "off" was not the severity of disability but the level of affect/arousal. The fluctuations in cognitive function found tended to be mild relative to the severe changes in motor ability, and were present in only a proportion of patients.